Computer Science concepts and applications - Halt, Tom (Willford Press, 2016)
This book is aimed to provide a comprehensive insight into the field of computer science. Computer science is a multidisciplinary field that incorporates both theory and applications of computations. It includes both framework and designing of computers as well as the modeling and analyses of various algorithms and programs that support different computational operations. It incorporates principles and concepts from various scientific disciplines like electrical engineering, physics and mathematics. This book is an assimilation of the various concepts and applications of computer science. The important topics elucidated in this comprehensive book includes different computational methodologies and techniques for solving complex tasks in various disciplines, assessment of existing information systems, artificial intelligence, soft computing, etc. The researches and case studies collated in this book aim to provide a coherent overview of the diverse concepts and applications of computer science at present. It is an excellent reference book for the students, researchers and experts involved in the field of computer science.